KEADILAN SEBAGAI MAQĀṢID AL-ḌARŪRIYYĀT DALAM KEBUTUHAN SOSIAL MODERN - MZ, Husamuddin; Efendi, Sumardi; Khamisan, Khamisan; Risaldi, Merta (Program Studi Hukum Keluarga dan Hukum Ekonomi Syariah, Program Pascasarjana Institut Agama Islam Negeri (IAIN) Ternate, 2023)
The reconstruction agenda occurred in the early era of the emergence of the theory of maqāṣid al-syarīah, starting from the era of Al-Syafi'ī who is considered to be the first figure to use the term maqāṣid al-syarīah, up to the era of Muhammad Al-Ṭāhir Ibn 'Āsyūr who tried to apply this theory in the world real. There is a change in construction in the theory of maqāṣid al-syarīah, following changes in the context of maqāṣid al-ḍarūriyyāt in Al-Kullīyāt Al-Khamsah. This research examines the value of justice as maqāṣid al-ḍaruriyyāt in modern social needs. This research is library research, with descriptive analysis methods. The research results found; Firstly, the construction of al-kulliyyat al-khamsah has essentially begun to have discussions and differences regarding the placement of the order of emergency levels in the early eras. Second, the fundamental values of maqāṣid al-syarī'ah have been concluded using inductive methods (istiqra') by figures such as Al-Ghazālī, 'Izz Al-Dīn Ibn 'Abd Al- Salām and Al-Syāṭibī. According to 'Abdullah Saeed, Muhammad Al-Ghazalī and Luai Ṣāfī, in the modern era a number of new values can be developed using the istiqra method', new human rights that are important today can contain the universality of values. One of the important and fundamental values in religious texts as part of human rights which is a modern social need is 'justice', making it relevant as a fundamental maqāṣid and as a maqāṣid kullī which includes various aspects of maqāṣid juz'ī.